US land policy, property rights, and the dust bowl of the 1930s - Gary D. Libecap; Zeynep K. Hansen (Fondazione Eni Enrico Mattei (FEEM), 2001)
The process of assigning property rights to land in the American Great Plains resulted in farms that were too small to be economically viable. These farms were prime contributors to the Dust Bowl of the 1930s. The path dependence resulting from the initial assignment of property rights on the Great Plains was slow to be corrected. The transactions costs of property rights reallocation from homesteads to larger farms were high, in part due to government intervention. Local politicians sought to retain the dense, Midwest-like population base that homestead settlement had fostered, and they successfully lobbied the Federal Government for subsidies to maintain small family farms. The result was a halting process of farm size adjustment between 1920 and 1982. This case illustrates the difficult economic problems that can be raised by an inappropriate assignment of property rights. It cannot be assumed that a more efficient allocation of rights with fewer negative effects will occur quickly.
Keywords: Q2; N4; N5; L5; 330; Property rights; Coase; Dust Bowl; Bodenpolitik; Eigentumsrechtstheorie; Grundbesitz; Umweltbelastung; Betriebsgröße; Anbausystem; Great Plains